The Effectiveness of Branding Campaigns on Social Media - Ningrum Resmawa, Ira; Masruroh, Siti; Maulida, Sofia (Journal of Management, 2024)
This study aims to evaluate the effectiveness of branding campaigns on social media by identifying the influence of various variables such as content type, content duration, social media platform, interaction, target audience, and budget on Brand Awareness. Using data from 100 respondents involved in branding campaigns on social media, this study applies multiple linear regression methods to analyze the relationship between independent variables and Brand Awareness as the dependent variable. The reliability of the research instrument, as measured by Cronbach's Alpha, reached 0.927, indicating very good internal consistency. The results of the analysis show that content duration and budget have a significant and positive effect on Brand Awareness, with p values ​​of 0.001 and 0.000, respectively. In contrast, the interaction and target audience variables do not show a significant effect, with p values ​​of 0.498 and 0.123, respectively. The regression model used shows an R² value of 0.594, indicating that 59.4% of the variation in Brand Awareness can be explained by the variables in the model. The ANOVA test supports the overall significance of the model with F value = 34.680 and p = 0.000.These findings highlight the importance of duration and budget in social media branding campaigns and provide valuable insights for marketers to design more effective strategies. This study recommends considering increasing the duration and budget allocation in branding campaigns and conducting further research to explore other factors that may affect Brand Awareness.